2011 International Conference on Electrical and Control Engineering 2011
DOI: 10.1109/iceceng.2011.6058225
|View full text |Cite
|
Sign up to set email alerts
|

Notice of Retraction Study on the influence of topography on mechanics effect of tunnels

Abstract: Based on special topography of the LiShan tunnel of the Hefei--Fuzhou passenger dedicated line in Wuyuan, Jiangxi province, this paper analyzes the vault settlement, surrounding rock stress, initial supporting axis force and supporting bending moment of slopes with different angles to the horizontal plane by the finite element method, which shows: keeping the overburden thickness of tunnel roof invariant, the vault settlement, surrounding rock stress, initial supporting axis force and supporting bending moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ere have been studies on the stress characteristics of surrounding rocks and tunnel support structures in tunnels [15][16][17][18][19]. e often adopted research methods were theoretical analysis and numerical simulation [20,21]. Adachsa concluded that surrounding rock pressure was affected by the tunnel construction method and surrounding rock deformation had an impact on stress distribution [22].…”
Section: Introductionmentioning
confidence: 99%
“…ere have been studies on the stress characteristics of surrounding rocks and tunnel support structures in tunnels [15][16][17][18][19]. e often adopted research methods were theoretical analysis and numerical simulation [20,21]. Adachsa concluded that surrounding rock pressure was affected by the tunnel construction method and surrounding rock deformation had an impact on stress distribution [22].…”
Section: Introductionmentioning
confidence: 99%